Edukasi Strategi Pendayagunaan ZISWAF untuk Kemandirian Ekonomi Jamaah di Pondok Pesantren Mambaul Ulum Al-Birowi - Aldi Khusmufa Nur Iman; Hawa Gazani; Clara Devy Yulvia Ratna Sary; Afaful Ummah; Afuza Medina (Institut Pesantren Sunan Drajat Lamongan, Indonesia, 2026)
Mosques have significant potential for the socio-economic empowerment of the community through the instruments of Zakat, Infaq, Sadaqah, and Waqf (ZISWAF). However, in reality, the management of these funds is often passive and consumptive, mostly allocated for physical maintenance. This community service activity aims to provide education and formulate a strategic framework for